Stress : An Owner's Manual - Rowshan, Arthur (Oxford England One World, 1997)
This guide offers a holistic approach to stress management, including spiritual, mental, emotional and physical stress. It offers a wide range of easily mastered techniques and mental skills for dealing with stress and its symptoms, including meditation and relaxation exercises.
Include Appendix and Index
Keywords: Stress management -- Stress (Psychology) -- Stress (Psychology)--Religious aspects